Trump, the administrative presidency, and federalism - Thompson, Frank J.; Wong, Kenneth K., 1955-; Rabe, Barry George, 1957- (Brookings Institution Press, 2020)
"The presidency of Donald Trump has been unique in many respects-most obviously his flamboyant personal style and disregard for conventional niceties. But one area hasn't received as much attention as it deserves: Trump's use of the "administrative presidency," including executive orders and regulatory changes, to reverse the policies of his predecessor and advance positions that lack widespread support in Congress. This book analyzes the dynamics and unique qualities of Trump's administrative presidency in the important policy areas of health care, education, and climate change. In each of these spheres, the arrival of the Trump administration represented a hostile takeover in which White House policy goals departed sharply from the more "liberal" ideologies and objectives of key agencies, which had been embraced by the Obama administration. Three expert authors show how Trump has continued, and even expanded, the rise of executive branch power since the Reagan years. The authors intertwine this focus with an in-depth examination of how the Trump administration's hostile takeover has drastically changed key federal policies-and reshaped who gets what from government-in the areas of health care, education, and climate change. Readers interested in the institutions of American democracy and the nation's progress (or lack thereof) in dealing with pressing policy problems will find deep insights in this book. Of particular interest is the book's examination of how the Trump administration's actions have long-term implications for American democracy"--